Activation of protease‐activated receptor 2 mediates cutaneous vasodilatation but not sweating: roles of nitric oxide synthase and cyclo‐oxygenase. Issue 2 (1st February 2017) - Fujii, Naoto; McNeely, Brendan D.; Zhang, Sarah Y.; Abdellaoui, Yasmine C.; Danquah, Mercy O.; Kenny, Glen P.
Abstract : New Findings: What is the central question of this study? Protease‐activated receptor 2 (PAR2) is located in the endothelial cells of skin vessels and eccrine sweat glands. However, a functional role of PAR2 in the control of cutaneous blood flow and sweating remains to be assessed in humans in vivo . What is the main finding and its importance? Our results demonstrate that in normothermic resting humans in vivo, activation of PAR2 elicits cutaneous vasodilatation partly through nitric oxide synthase‐dependent mechanisms, but does not mediate sweating. These results provide important new insights into the physiological significance of PAR2 in human skin. Protease‐activated receptor 2 (PAR2) is present in human skin, including keratinocytes, endothelial cells of skin microvessels and eccrine sweat glands. However, whether PAR2 contributes functionally to the regulation of cutaneous blood flow and sweating remains entirely unclear in humans in vivo . We hypothesized that activation of PAR2 directly stimulates cutaneous vasodilatation and sweating via actions of nitric oxide synthase (NOS) and cyclo‐oxygenase (COX). In 12 physically active young men (29 ± 5 years old), cutaneous vascular conductance (CVC) and sweat rate were measured at four intradermal microdialysis forearm skin sites that were treated with the following: (i) lactated Ringer's solution (control); (ii) 10 mm N G ‐nitro‐l ‐arginine (NOS inhibitor); (iii) 10 mm ketorolac (COX inhibitor); or (iv) a combination of both inhibitors. At all sites, a PAR2 agonist (SLIGKV‐NH2 ) was co‐administered in a dose‐dependent fashion (0.06, 0.18, 0.55, 1.66 and 5 mm, each for 25 min). The highest dose of SLIGKV‐NH2 (5 mm ) increased CVC from baseline at the control site ( P ≤ 0.05). This increase in CVC associated with PAR2 activation was attenuated by NOS inhibition regardless of the presence or absence of simultaneous COX inhibition (both P ≤ 0.05). However, COX inhibition alone did not affect the PAR2‐mediated increase in CVC ( P > 0.05). No increase in sweat rate was measured at any administered dose of SLIGKV‐NH2 (all P > 0.05). We show that in normothermic resting humans in vivo, PAR2 activation does not increase sweat rate, whereas it does modulate cutaneous vasodilatation through NOS‐dependent mechanisms. Abstract :